2021
DOI: 10.1016/j.ijrobp.2021.05.133
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Randomized Trial of Topical Steroid Versus Placebo for Prevention of Radiation Dermatitis in Patients With Head and Neck Cancer Receiving Chemoradiation

Abstract: Phase 3 randomized trial of topical steroid versus placebo for prevention of radiation dermatitis in head and neck cancer patients receiving chemoradiation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The standard radiation dose of CRT for HNC is 70 Gy in 35 fractions (fr) for the definitive setting and 60 to 66 Gy in 30 to 33 fr for the postoperative setting. In a recent phase III clinical trial, Yokota et al (9) provide evidence that topical steroids have the potential to lessen the serious nature of radiation dermatitis and thereby become an important therapeutic tool in managing radiation dermatitis induced by high-dose irradiation with chemotherapy in the care of head and neck cancer (HNC).…”
Section: Topical Steroids and Non-steroid Agentsmentioning
confidence: 99%
“…The standard radiation dose of CRT for HNC is 70 Gy in 35 fractions (fr) for the definitive setting and 60 to 66 Gy in 30 to 33 fr for the postoperative setting. In a recent phase III clinical trial, Yokota et al (9) provide evidence that topical steroids have the potential to lessen the serious nature of radiation dermatitis and thereby become an important therapeutic tool in managing radiation dermatitis induced by high-dose irradiation with chemotherapy in the care of head and neck cancer (HNC).…”
Section: Topical Steroids and Non-steroid Agentsmentioning
confidence: 99%
“…157 Topical cutaneous steroids do confer benefit for reducing radiation dermatitis in patients with head and neck cancer who are receiving chemoradiation, however. 158…”
Section: Head and Neck Oncologymentioning
confidence: 99%
“…While some studies have suggested a possible role for use of SCSs, a systematic review of this literature determined that no definitive conclusions could be reached based on the low quality of evidence 157 . Topical cutaneous steroids do confer benefit for reducing radiation dermatitis in patients with head and neck cancer who are receiving chemoradiation, however 158 …”
Section: Head and Neck Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…At present, about 95% of patients who receive radiation therapy will develop RD ( Rosenthal et al, 2019 ). Patients with breast cancer, head and neck cancer, lung cancer, or sarcoma are more likely to suffer from RD ( Fuzissaki et al, 2019 ; Tinkle et al, 2021 ; Yokota et al, 2021 ; Louie et al, 2022 ). Erythema is the predominant sign among RD patients, while 42 and 15% of patients developed RT-induced grade 3 and 4 skin toxicities characterized by desquamation, ulceration, and pigment changes ( Hu et al, 2018 ; Bontempo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%